The Role of Digitalization In Improving Human Resources Management Performance at PT. Semen Indonesia Unit Tonasa in Makassar City - Rostini; Ibadurrahman; Syahribulan; Rahman, Fatmawati A (Economics and Business Journal (ECBIS), 2024)
The digitalization of Human Resource Management (HRM) at PT. Semen Indonesia Unit Tonasa has significantly transformed the company’s HR operations, improving efficiency and effectiveness across various HR functions. Located in Makassar, PT. Semen Indonesia Unit Tonasa, a major player in the cement manufacturing industry, faced challenges in managing its large and diverse workforce, including slow recruitment processes, inconsistent performance evaluations, and inefficient data management. To address these challenges, the company adopted cloud-based HR management systems, automated recruitment tools, and performance management software, allowing for real-time monitoring and data-driven decision-making. The results of this digital transformation were notable: recruitment time was reduced by 30%, performance evaluations became more transparent and objective, and employee engagement increased through self-service portals and online learning platforms. The integration of real-time data analytics enabled HR managers to make more informed decisions, aligning HR practices with organizational goals. Despite facing resistance to change and technical challenges related to system integration, the company effectively managed the transition through comprehensive training and ongoing support. This study demonstrates how digital tools can optimize HR processes, enhance employee satisfaction, and improve organizational performance. The success of PT. Semen Indonesia Unit Tonasa’s digital HR implementation provides valuable insights for other organizations seeking to modernize their HR functions in an increasingly digital and competitive environment